Does acute improvement in muscle recovery with Curcumin supplementation translate to long-term training? - McFarlin, B. K.; Tanner, E. A.; Gary, M. A.; Davis, A. A.; Bowman, E. M.; Gary, R. S. (Journal of Science in Sport and Exercise, 2019)
Dietary polyphenols, such as curcumin, green tea catechins, and pomegranate extract, may have the ability to enhance the effectiveness of long-term training programs by managing training-induced inflammation. Enhanced recovery may translate to increased capacity to train and perform more effectively. The dietary polyphenol curcumin has been reported to block the action of COX-2 and NF-kB signaling and would allow for increased capacity to train leading to heightened adaptations and the potential for ergogenic outcomes. These actions are very similar to the targeted actions of non-steroidal anti-inflammatory drugs (NSAIDs), but without the side-effects of NSAIDs. This review will compare and contrast the known effects of curcumin and identify common design elements between existing studies. Through this critical review of the existing literature it is our goal to establish a set of best practices that could be applied to an athletic population that is interested in using oral curcumin supplementation as a recovery agent.